SUMINI LEDHEK BARANGAN DARI SUKOREJO, KEDUNG JERUK, MOJOGEDANG, KABUPATEN KARANGANYAR - S., Sudarno (Institut Seni Indonesia Surakarta, 2015)
The object of this research is Sumini, a woman from the village of Sukorejo, in the KedungJeruk, sub-district of Mojogedang, in the district of Karanganyar, whose profession is a Ledhek barangan artist. The research aims to discover Suminiâ€™s journey to become a Ledhek baranganartist and her style of movements when performing, or â€œmbarang Ledhekâ€. It is a qualitativeresearch study which uses a choreographic approach. In order to analyze Suminiâ€™s journey to become a Ledhek barangan artist, T. Inrahim Alfianâ€™s theory of history is used. In order to analyzeSuminiâ€™s style of movements, the writer uses Desmond Morrisâ€™s theory, as quoted and presentedby Soedarsono. Due to her skill and perseverance, Sumini has managed to create a unique style ofmovement in her performance of Ledhek barangan, such as movements that are performed witha large volume and a technique in which the left foot is positioned on tiptoe(gejuk)behind theright foot.Keywords: Ledhek barangan, Sumber Laras, Sumini.